Simulation and Analysis of Piezoelectric Energy Harvester with Various Proof-Mass Geometries - B, Sirisha; Santhosh, Chella; S, Sunithamani; M, Ravi Kumar; J, Lakshmi Prasanna (International Journal of Online and Biomedical Engineering (iJOE), 2022)
This paper aims to generate electricity, by decreasing fossil fuels consumption and conserving electricity for further use. In this project, the method is to produce pollution-free electricity using the technique i.e. piezoelectric effect technique. By applying mechanical stress electric charge is generated known as the piezoelectric effect. A sufficient amount of energy is produced as it can reduce the damage of pollution caused by power plants. So to make the use of moving vehicles on road, power generated helps the environment last longer. Different shape, proof mass geometries are analyzed and plotted a graph between frequency versus voltage and electrical energy. Among them, it is identified that stacked cylindrical block has a good Voltage of 2.04mV (milliVolts = 10-3V) and Energy of 21.2fJ (femtoJoule = 10-15J).